"All Those Ingredients of the Walk": The Therapeutic Spaces of Dog-walking for People with Long-term Health Conditions. (3rd April 2017) - Smith, Catherine M.; Treharne, Gareth J.; Tumilty, Steve
ABSTRACT: We currently know little about how dog-walking contributes to health and wellbeing of adults living with long-term health conditions. Guided by a conceptual framework of "therapeutic mobilities, " we accompanied 13 adults with diverse long-term health conditions on their usual dog-walk. We captured conversations about health and wellbeing through audio-recordings. Interactions with environment, other humans, and between humans and dogs were captured via video-recordings. We provided each participant with a transcript and video-recording of the dogwalk-along interview and met all participants again for a further seated interview. Guided by participants, we developed a series of themes: a special relationship, motivation (an obligation of love), social isolation and connections, and the dog-walk recipe. From these themes, we developed a model of inter-linked and fluid "therapeutic spaces" through which dogwalking can enhance or diminish wellbeing in people with long-term health conditions. Humans with long-term health conditions develop close relationships with their dogs. This "obligation of love" takes humans in to the Dog-walk space where gentle encounters and pleasant sensations enhance human wellbeing. Further research will identify ways in which people with long-term health conditions might further access dog-walking therapeutic spaces, thereby enhancing therapeutic encounters with other humans, dogs, and the environment.